Dakwah Pemberdayaan Berbasis Konservasi dan Pariwisata Melalui Volunteer Tapak Abdi Negeri di Desa Sriharjo Yogyakarta - Fadilah, Anisatul; Hidayatullah, Ahmad; Taufiq, Ahmad (STAIN SULTAN ABDURRAHMAN KEPRI, 2025)
Currently, da’wah activities are very diverse, one of which is the volunteer program, Tapak Abdi Negeri Volunteers have a significant role in empowering the community in Yogyakarta, by involving individuals in various social activities and community development programs. This study aims to analyze the impact of their participation on improving the quality of life of the local community. To achieve this goal, a qualitative method was used which included in-depth interviews and participant observation. The results of the study showed that activities initiated by Tapak Abdi Negeri Volunteers, such as skills training, entrepreneurship development, and increasing environmental awareness, have succeeded in empowering the community. In addition, volunteers function as a bridge between the community and the government, thus strengthening social relations and collaboration between parties. These findings underline the importance of the role of volunteers in encouraging positive social change. Thus, this study is expected to be a reference for the development of similar programs in other areas.